Modelowanie ryzyka upadłości a metody oceny efektywności wybranych modeli - Strycharczyk, Agnieszka (Bankruptcy Risk Modeling and Methods of Forecasting the Risk, 2007)
The issue of bankruptcy of Polish enterprises receives growing attention - especially when concerning on the main issues banks will have to face to comply with the new Basel II internal ratings-based approach. Therefore bankruptcy risk assessment models are in the center of interest as well as the methods of their quality measurement. Due to a variety of technical developments in finance, it has become possible both to quantify the level of default risk in a single asset and test the model's accuracy - simply defined as a model's ability to correctly classify firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 529-535